Autoimmune GFAP astrocytopathy after viral encephalitis: a case report of bimodal overlapping encephalitis - Cheng, Ping; Huang, Wenjuan; Yang, Meifang; Chen, Zhiren; Geng, Yifan; Zhang, Xia; Chen, Weiwei (Frontiers in Immunology, 2023)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a treatable autoimmune disorder affecting the central nervous system. Despite extensive research, the exact etiology and pathogenesis of this condition remain unclear. In recent years, autoimmune encephalitis (AE) after viral encephalitis (VE) has gathered significant attention. Here, we present a case report of autoimmune GFAP astrocytopathy after VE in a 43-year-old Asian male with a history of oral and labial herpes. The patient presented with high-grade fever, headache, urinary retention, unresponsiveness, and apathy. Elevated levels of protein and GFAP-IgG were observed in the cerebrospinal fluid (CSF), and enhanced brain magnetic resonance imaging (MRI) revealed linear enhancement oriented radially to the ventricles. Treatment with intravenous immunoglobulin (IVIG) resulted in symptom relief, reduced lesion enhancement, and decreased protein levels. This case report highlights bimodal encephalitis with no discernible interval between VE and autoimmune GFAP astrocytopathy, which poses diagnostic challenges.Notably, autoimmune GFAP astrocytopathy is a novel form of autoimmune encephalitis, and its treatment lacks sufficient clinical experience. Intriguingly, our patient demonstrated sensitivity to IVIG, a treatment that differed from past reports. Therefore, further exploration of treatment strategies for this condition is warranted.